Antibiotics in Crop Production - Leigh Archer; Ute Albrecht; Pamela Roberts (EDIS)
This new 5-page article presents an overview of the use of antibiotics in agriculture. Several of the most severe bacterial diseases of tree fruit and other crops are discussed and their integrated management, which includes the use of antibiotics, is described. Antibiotic use for plant disease protection is compared with the use of antibiotics in livestock production, and their future and limitations in plant production are discussed. Written by  Leigh Archer, Ute Albrecht, and Pamela Roberts, and published by the UF/IFAS Horticultural Sciences Department.